18F-FDG and 18F-NaF PET/CT demonstrate coupling of inflammation and accelerated bone turnover in rheumatoid arthritis. Issue 2 (3rd March 2016) - Watanabe, Toshiyuki; Takase-Minegishi, Kaoru; Ihata, Atsushi; Kunishita, Yosuke; Kishimoto, Daiga; Kamiyama, Reikou; Hama, Maasa; Yoshimi, Ryusuke; Kirino, Yohei; Asami, Yukiko; Suda, Akiko; Ohno, Shigeru; et al.
Abstract : Objective. To compare the findings in rheumatoid arthritis (RA)-affected joints between 18 F-fluorodeoxyglucose (FDG) and 18 F-fluoride (NaF) positron emission tomography (PET)/computed tomography (CT). Methods. We enrolled twelve RA patients who started a new biologic agent (naïve 9 and switch 3). At entry, both hands were examined by 18 F-FDG PET/CT, 18 F-NaF PET/CT, and X-ray. Intensity of PET signals was determined by standardized uptake value max (SUVmax) in metacarpophalangeal (MCP), proximal interphalangeal (PIP), and ulnar, medial, and radial regions of the wrists. Hand X-rays were evaluated according to the Genant-modified Sharp score at baseline and 6 months. Results. Both 18 F-FDG and 18 F-NaF accumulated in RA-affected joints. The SUVmax of 18 F-FDG correlated with that of 18 F-NaF in individual joints ( r = 0.65), though detail distribution was different between two tracers. 18 F-NaF and 18 F-FDG signals were mainly located in the bone and the surrounding soft tissues, respectively. The sum of SUVmax of 18 F-NaF correlated with disease activity score in 28 joint (DAS28), modified health assessment questionnaire (MHAQ), and radiographic progression. 18 F-FDG and 18 F-NaF signals were associated with the presence of erosions, particularly progressive ones. Conclusion. Our data show that both 18 F-FDG and 18 F-NaF PET signals were associated with RA-affected joints, especially those with ongoing erosive changes.